(untitled) (Rupandehi Campus Journal, 2022)
Noam Chomsky revolutionized the study of linguistics when his book Syntactic Structures was published in 1957. This book gave birth to the idea of generative grammar, which is a theory about language structure. This grammar made a distinction between deep structure and surface structure, something like what Saussure called langue and parole. Chomsky claimed that language structure is innate or genetically inherited. Consequently, structure is to be found inside the organism and the hypothesis is that we learn language because we are born with a Universal Grammar (hereafter referred as UG) in our head. This study aims to find out if UG is real or just an invention. In order to find the strengths and weaknesses with such a controversial statement, this paper will compare Chomsky’s theories when it comes to language acquisition to the behaviorists’ and the modern cognitive linguistics’ approach to the problem. But before the comparison this paper will explain in detail about the shift of focus in the approach to problems of language. Then, it will present an overview of how language and, in particular, language acquisition was explained by the structuralists and by Chomsky.